A composite flocculant for treating surface water and preparation method thereof

By modifying polymer chitosan, introducing hydrophilic groups and forming a complex network structure, the problems of poor stability and flocculation effect of natural polymer flocculants are solved, and efficient flocculation effect is achieved under different pH and water quality conditions.

CN118909192BActive Publication Date: 2025-03-14内蒙古森鼎环保节能股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411415512.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The stability and flocculation effect of natural polymer flocculants are poor, and are sensitive to the pH, temperature and chemical conditions of water bodies, making it difficult to control the flocculation effect.

Method used

The polymer chitosan is used as a matrix, and a large number of hydrophilic groups are introduced through the modification of polygroup acrylamide to improve the solubility of chitosan in different pHs, and a complex network structure is formed by phosphorylation of acrylate compounds and N,N’-bis(acryl)cysamine to enhance flocculation performance.

Benefits of technology

The modified composite flocculant has a more stable flocculation effect, which can effectively flocculate particles of various particle sizes, expand the application range, and show high stability and efficiency under different water quality conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909192B_ABST
    Figure CN118909192B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite flocculant for treating surface water in the field of surface water treatment technology and a preparation method thereof. The composite flocculant uses high molecular chitosan as a matrix, is modified by multi-group acrylamide, and introduces a large number of hydrophilic groups and quaternary amine groups into the chitosan high molecular matrix, thereby improving the solubility of high molecular chitosan in water environments with different pH values. The modified composite flocculant has a complex network structure, which is distributed in active groups and can effectively flocculate particles of various particle sizes in sewage, thereby expanding the application scope of the composite flocculant. The matrix of the composite flocculant of the present invention is chitosan, which is non-toxic and friendly to the environment, and will not cause secondary pollution to the water environment. The composite flocculant overcomes the large amount of heavy metal residues caused by inorganic flocculants, and has high performance in absorbing a variety of pollutants. After sewage flocculation, the treatment and recovery steps of the formed conjugate are simple, thereby reducing the cost of water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface water treatment, and specifically refers to a composite flocculant for treating surface water and a preparation method thereof. Background Art

[0002] Water treatment technology is the process of removing pollutants from water by physical, chemical and biological means to achieve purification, reuse or discharge standards; At present, water treatment technologies mainly include coagulation technology, flocculation technology, adsorption technology, oxidation technology, membrane filtration technology and evaporation technology. Among them, flocculation is a physical separation process that combines and aggregates solid particles in liquid to form larger floccules. It has the characteristics of low cost, simple use and less sludge production; Flocculation technology includes two treatment methods: direct flocculation and indirect flocculation. Direct flocculation refers to adding coagulants directly to water bodies, and through chemical reactions, the suspended particles and colloids in the water are aggregated into larger floccules, which are then removed by sedimentation or filtration. This method does not require special pretreatment or other external auxiliary measures, and relies on the effect of the coagulant itself. It is often used for water sources with relatively clear water quality and fewer suspended particles, such as drinking water pretreatment and low-pollution domestic sewage treatment; indirect flocculation usually refers to pretreatment or auxiliary treatment of water bodies before or during the addition of coagulants to enhance the flocculation effect. This pretreatment may include adjusting the pH value, adding coagulants, increasing the reaction time or using electrochemical methods to improve the effect of the coagulant and make the flocculation effect better. It is often used in the treatment of complex water quality such as industrial wastewater, oily wastewater or high turbidity wastewater, or the water quality has a high concentration of colloidal substances, or the chemical properties of the water need to be adjusted to improve the flocculation effect. Commonly used flocculants include inorganic flocculants and organic flocculants. Considering the problem of environmental residues, natural polymer flocculants have greater advantages; however, the sources of natural polymer flocculants are complex, and there may be differences in molecular weight, structure and activity between different batches, resulting in unstable flocculation effect and difficulty in control. At the same time, natural polymer flocculants are sensitive to the pH value, temperature and other chemical conditions of the water body, and the effect may fluctuate under different water quality conditions. The mechanical properties of natural polymer materials are weak and are easily affected by mechanical stress or shear force, which leads to the breakage of the molecular chain of the flocculant and affects the flocculation effect. Summary of the invention

[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a composite flocculant for treating surface water and a preparation method thereof. In order to solve the problems of poor stability and flocculation effect of natural polymer flocculants, the composite flocculant of the present invention uses polymer chitosan as a matrix, is modified by multi-group acrylamide, and a large number of hydrophilic groups are introduced into the chitosan polymer matrix to improve the solubility of the polymer chitosan in water environments with different pH values. The modified composite flocculant has a complex network structure distributed in the active groups, can effectively flocculate particles of various particle sizes in sewage, and expand the application range of the composite flocculant.

[0004] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: The present invention proposes a composite flocculant for treating surface water, wherein the raw materials for preparing the composite flocculant include the following components in parts by weight: 10-15 parts of Fe3O4 / chitosan, 30-40 parts of phosphorylated acrylate compound, 4-5 parts of N,N'-bis(acryl)cystamine, and 1-2 parts of initiator;

[0005] Preferably, the synthetic raw materials of the phosphated acrylate compound include the following components in parts by weight: 4-5 parts of 2-aminoethyl methacrylate hydrochloride, 10-12 parts of dimethyl phosphite, and 1-2 parts of formaldehyde;

[0006] Preferably, the initiator comprises at least one of potassium persulfate and sodium persulfate;

[0007] The present invention also provides a method for preparing a composite flocculant for treating surface water, which specifically comprises the following steps:

[0008] S1. Dissolve chitosan in acetic acid solution, add ferric chloride and ferrous chloride, stir and react until the reaction system turns brown, add 2 mol / L NaOH solution and 0.2 mol / L sodium citrate solution, mix well, age for 8-12 hours, and wash with deionized water until neutral to obtain Fe3O4 / chitosan;

[0009] Preferably, in step S1, the mass concentration of chitosan in the acetic acid solution is 20-30 g / L; the volume fraction of acetic acid in the acetic acid solution is 1%-2%;

[0010] Preferably, in step S1, the mass ratio between the ferric chloride and the ferrous chloride is 1:1.5-2;

[0011] Preferably, in step S1, the mass ratio between chitosan and ferric chloride is 1:1.5-1.8;

[0012] Preferably, in step S1, the volume ratio between the NaOH solution and the acetic acid solution is 1:2.5-3; the volume ratio between the sodium citrate solution and the acetic acid solution is 1:2-2.3;

[0013] S2, placing 2-aminoethyl methacrylate hydrochloride in a 95 vol% ethanol solution, stirring at a speed of 150 rpm until completely dissolved, adding dimethyl phosphite and mixing evenly, raising the temperature to 60-70°C, adding formaldehyde solution, mixing evenly, adding sodium p-toluenesulfonate, maintaining the reaction temperature at 70-80°C, and performing reflux reaction for 4-6 hours. After the reaction is completed, the reaction system is cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol and deionized water, and freeze-dried to obtain a phosphorylated acrylate compound;

[0014] Preferably, in step S2, the mass concentration of 2-aminoethyl methacrylate hydrochloride in the ethanol solution is 10-15 g / L;

[0015] Preferably, in step S2, the mass fraction of formaldehyde in the formaldehyde solution is 37%;

[0016] Preferably, in step S2, the added mass of the sodium p-toluenesulfonate is 10%-12% of the mass of 2-aminoethyl methacrylate hydrochloride;

[0017] S3, placing the Fe3O4 / chitosan prepared in step S1 in a 75 vol% ethanol solution, adding acetic acid, and mixing thoroughly, introducing nitrogen into the reaction system, adding an initiator, and continuing to stir to make the reaction system uniform, adding the phosphorylated acrylate compound and N,N'-bis(acryl)cystamine prepared in step S2, raising the reaction temperature to 50-60°C, reacting for 3-4h, cooling the reaction system to room temperature, adding anhydrous ethanol for treatment, centrifuging at 4500-6000rpm for 3-5min, discarding the supernatant, washing the lower layer of the reaction product with anhydrous ethanol, and drying to obtain a composite flocculant;

[0018] Preferably, in step S3, the mass concentration of the Fe3O4 / chitosan in the ethanol solution is 10-20 g / L;

[0019] Preferably, in step S3, the added volume of acetic acid is 1%-2% of the volume of the ethanol solution.

[0020] The beneficial effects achieved by the present invention are as follows:

[0021] The invention provides a composite flocculant for treating surface water. The composite flocculant of the invention uses high molecular chitosan as a matrix, is modified by multi-group acrylamide, and introduces a large number of hydrophilic groups into the chitosan high molecular matrix, thereby improving the solubility of the high molecular chitosan in water environments with different pH values. The modified composite flocculant has a complex network structure distributed in active groups, and can effectively flocculate particles of various particle sizes in sewage, thereby expanding the application range of the composite flocculant. The invention forms a composite material with chitosan and magnetic Fe3O4, and polymerizes acrylic acid polymers by grafting amino groups of chitosan. The acrylic acid polymer is composed of phosphorylated acrylate compounds and N,N'-bis(propylene) The invention relates to a method for preparing a composite flocculant of the present invention. ... BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the infrared spectrum analysis diagram of the composite flocculant and chitosan prepared in Example 1;

[0023] Figure 2 This is a microscopic morphology image of the composite flocculant prepared in Example 1;

[0024] Figure 3 The Zeta potential result diagram of the composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 at different pH values;

[0025] Figure 4 The flocculation performance and circulation performance of the composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3.

[0026] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.

[0030] Example 1

[0031] This embodiment provides a composite flocculant for treating surface water. The raw materials for preparing the composite flocculant include the following components in parts by weight: 10 parts of Fe3O4 / chitosan, 40 parts of phosphorylated acrylate compound, 4 parts of N,N'-bis(acryl)cystamine, and 2 parts of potassium persulfate;

[0032] The synthetic raw materials of the phosphating acrylate compound include the following components in parts by weight: 4 parts of 2-aminoethyl methacrylate hydrochloride, 12 parts of dimethyl phosphite, and 2 parts of formaldehyde;

[0033] This embodiment also provides a method for preparing a composite flocculant for treating surface water, which specifically comprises the following steps:

[0034] S1. Accurately weigh 1.0 g of chitosan and place it in a beaker. Prepare 1 vol% acetic acid solution. Take 50 mL of acetic acid solution and add it to the beaker. Place it on a magnetic stirrer and stir at 150 rpm until the chitosan is completely dissolved in the acetic acid solution. Accurately weigh 1.5 g of ferric chloride and 3.0 g of ferrous chloride and add them to the reaction system. Continue stirring until the reaction system turns brown. Prepare 2 mol / L NaOH solution and 0.2 mol / L sodium citrate solution. Take 20 mL of NaOH solution and 25 mL of sodium citrate solution and mix them evenly. Then, add them dropwise to the reaction system and continue stirring until they are evenly mixed. After aging for 12 h, wash with deionized water until neutral. After freeze-drying, Fe3O4 / chitosan is obtained.

[0035] S2. Accurately weigh 4 g of 2-aminoethyl methacrylate hydrochloride, add 400 mL of 95 vol% ethanol solution, place on a magnetic stirrer and mix at a speed of 150 rpm until 2-aminoethyl methacrylate hydrochloride is completely dissolved in the ethanol solution, add 10 mL of dimethyl phosphite, continue to stir and mix, raise the temperature to 65° C., add 5.4 mL of formaldehyde solution, the mass fraction of commercially available formaldehyde solution is 37%, add 0.4 g of sodium p-toluenesulfonate, raise the reaction temperature to 75° C., and reflux for 5 hours. After the reaction is completed, cool the reaction system to room temperature, distill under reduced pressure, wash repeatedly with anhydrous ethanol and deionized water three times, and freeze-dry to obtain a phosphorylated acrylate compound;

[0036] S3. Accurately weigh 1.0 g of the Fe3O4 / chitosan prepared in step S1 and place it in a flask, add 100 mL of 75 vol% ethanol solution, add 1 mL of acetic acid to the reaction system, increase the temperature to 40°C, stir at 180 rpm until the Fe3O4 / chitosan is evenly dispersed in the reaction system, introduce nitrogen into the reaction system, add 0.2 g of potassium persulfate, continue mixing for 5 min to fully dissolve the potassium persulfate, add 4.0 g of phosphorylated acrylate compound and 0.4 g of N,N'-bis(acryl)cystamine to the reaction system, increase the reaction temperature to 60°C, react for 3 h, wait for the reaction system to cool to room temperature, add 400 mL of anhydrous ethanol for washing, centrifuge at 5000 rpm for 5 min, discard the supernatant, wash the lower layer of the reaction product with anhydrous ethanol and deionized water three times in sequence, and dry to obtain a composite flocculant.

[0037] Example 2

[0038] This embodiment provides a composite flocculant for treating surface water. The raw materials for preparing the composite flocculant include the following components in parts by weight: 15 parts of Fe3O4 / chitosan, 30 parts of phosphorylated acrylate compound, 5 parts of N,N'-bis(acryl)cystamine, and 1 part of sodium persulfate;

[0039] The synthetic raw materials of the phosphating acrylate compound include the following components in parts by weight: 5 parts of 2-aminoethyl methacrylate hydrochloride, 10 parts of dimethyl phosphite, and 1 part of formaldehyde;

[0040] This embodiment also provides a method for preparing a composite flocculant for treating surface water, which specifically comprises the following steps:

[0041] S1. Accurately weigh 1.5 g of chitosan and place it in a beaker. Prepare 2 vol% acetic acid solution. Take 50 mL of acetic acid solution and add it to the beaker. Place it on a magnetic stirrer and stir at 150 rpm until the chitosan is completely dissolved in the acetic acid solution. Accurately weigh 2.7 g of ferric chloride and 4.0 g of ferrous chloride and add them to the reaction system. Continue stirring until the reaction system turns brown. Prepare 2 mol / L NaOH solution and 0.2 mol / L sodium citrate solution. Take 16.7 mL of NaOH solution and 21.7 mL of sodium citrate solution and mix them evenly. Then, add them dropwise to the reaction system and continue stirring until they are evenly mixed. After aging for 8 h, wash with deionized water until neutral. After freeze-drying, Fe3O4 / chitosan is obtained.

[0042] S2. Accurately weigh 4.5 g of 2-aminoethyl methacrylate hydrochloride, add 300 mL of 95 vol% ethanol solution, place on a magnetic stirrer and mix at a speed of 150 rpm until 2-aminoethyl methacrylate hydrochloride is completely dissolved in the ethanol solution, add 7.5 mL of dimethyl phosphite, continue to stir and mix, raise the temperature to 60° C., add 2.4 mL of formaldehyde solution, the mass fraction of commercially available formaldehyde solution is 37%, add 0.54 g of sodium p-toluenesulfonate, raise the reaction temperature to 80° C., and reflux for 4 hours. After the reaction is completed, cool the reaction system to room temperature, distill under reduced pressure, wash repeatedly with anhydrous ethanol and deionized water three times, and freeze-dry to obtain a phosphorylated acrylate compound;

[0043] S3. Accurately weigh 1.5 g of Fe3O4 / chitosan prepared in step S1 and place it in a flask, add 100 mL of 75 vol% ethanol solution, add 1.5 mL of acetic acid to the reaction system, increase the temperature to 40°C, stir at 180 rpm until Fe3O4 / chitosan is evenly dispersed in the reaction system, introduce nitrogen into the reaction system, add 0.1 g of sodium persulfate, continue mixing for 5 min to fully dissolve the potassium persulfate, add 3.0 g of phosphorylated acrylate compound and 0.5 g of N,N'-bis(acryl)cystamine to the reaction system, increase the reaction temperature to 50°C, react for 4 h, wait for the reaction system to cool to room temperature, add 400 mL of anhydrous ethanol for washing, centrifuge at 4500 rpm for 5 min, discard the supernatant, wash the lower layer of the reaction product repeatedly with anhydrous ethanol and deionized water three times in sequence, and dry to obtain a composite flocculant.

[0044] Example 3

[0045] This embodiment provides a composite flocculant for treating surface water. The raw materials for preparing the composite flocculant include the following components in parts by weight: 12 parts of Fe3O4 / chitosan, 36 parts of phosphorylated acrylate compound, 4.5 parts of N,N'-bis(acryl)cystamine, and 1.5 parts of potassium persulfate;

[0046] The synthetic raw materials of the phosphating acrylate compound include the following components in parts by weight: 4 parts of 2-aminoethyl methacrylate hydrochloride, 10 parts of dimethyl phosphite, and 1.5 parts of formaldehyde;

[0047] This embodiment also provides a method for preparing a composite flocculant for treating surface water, which specifically comprises the following steps:

[0048] S1. Accurately weigh 2 g of chitosan and place it in a beaker. Prepare 1.5 vol% acetic acid solution. Take 100 mL of acetic acid solution and add it to the beaker. Place it on a magnetic stirrer and stir at 150 rpm until the chitosan is completely dissolved in the acetic acid solution. Accurately weigh 3.2 g of ferric chloride and 4.8 g of ferrous chloride and add them to the reaction system. Continue stirring until the reaction system turns brown. Prepare 2 mol / L NaOH solution and 0.2 mol / L sodium citrate solution. Take 30 mL of NaOH solution and 45 mL of sodium citrate solution and mix them evenly. Then, add them dropwise to the reaction system and continue stirring until they are evenly mixed. After aging for 10 h, wash with deionized water until neutral. After freeze-drying, Fe3O4 / chitosan is obtained.

[0049] S2. Accurately weigh 3.6 g of 2-aminoethyl methacrylate hydrochloride, add 300 mL of 95 vol% ethanol solution, place on a magnetic stirrer and mix at a speed of 150 rpm until 2-aminoethyl methacrylate hydrochloride is completely dissolved in the ethanol solution, add 7.5 mL of dimethyl phosphite, continue to stir and mix, raise the temperature to 70°C, add 3.6 mL of formaldehyde solution, the mass fraction of commercially available formaldehyde solution is 37%, add 0.4 g of sodium p-toluenesulfonate, raise the reaction temperature to 70°C, and reflux for 6 hours. After the reaction is completed, cool the reaction system to room temperature, distill under reduced pressure, wash repeatedly with anhydrous ethanol and deionized water three times, and freeze-dry to obtain a phosphorylated acrylate compound;

[0050] S3. Accurately weigh 2 g of Fe3O4 / chitosan prepared in step S1 and place it in a flask, add 100 mL of 75 vol% ethanol solution, add 1 mL of acetic acid to the reaction system, increase the temperature to 40°C, stir at 180 rpm until Fe3O4 / chitosan is evenly dispersed in the reaction system, introduce nitrogen into the reaction system, add 0.25 g of potassium persulfate, continue mixing for 5 min to fully dissolve the potassium persulfate, add 6 g of phosphorylated acrylate compound and 0.75 g of N,N'-bis(acryl)cystamine to the reaction system, increase the reaction temperature to 55°C, react for 4 h, wait for the reaction system to cool to room temperature, add 400 mL of anhydrous ethanol for washing, centrifuge at 6000 rpm for 3 min, discard the supernatant, wash the lower layer of the reaction product repeatedly three times with anhydrous ethanol and deionized water in sequence, and dry to obtain a composite flocculant.

[0051] Comparative Example 1

[0052] This comparative example provides a composite flocculant and a preparation method thereof, which differs from Example 1 only in that the phosphacylated acrylate compound in the preparation raw material of the composite flocculant is replaced by the same weight portion of 2-aminoethyl methacrylate hydrochloride, and the preparation method does not include step S2. The components, component contents and preparation method are the same as those of Example 1.

[0053] Comparative Example 2

[0054] This comparative example provides a composite flocculant and a preparation method thereof, which differs from Example 1 only in that N,N'-bis(acryl)cystamine in the preparation raw material of the composite flocculant is replaced by N,N'-vinylbisacrylamide in the same weight portion, and its components, component contents and preparation method are the same as those in Example 1.

[0055] Comparative Example 3

[0056] This comparative example provides a composite flocculant and a preparation method thereof, which differs from Example 1 only in that Fe3O4 / chitosan in the raw materials for preparing the composite flocculant is replaced with chitosan of the same weight, and the preparation method does not include step S1, and the components, component contents and preparation method are the same as those in Example 1.

[0057] Experimental Example 1

[0058] In this experimental example, the composite flocculant prepared in Example 1 was characterized by infrared spectroscopy. Equal amounts of chitosan and the composite flocculant prepared in Example 1 were ground evenly with KBr, pressed into tablets to prepare samples, and the chemical structure and functional group analysis of the samples was performed using a Nicolet 380 Fourier transform infrared spectrometer.

[0059] Figure 1 The infrared spectrum analysis of the composite flocculant and chitosan prepared in Example 1 is shown in the figure, where Image 1 is the infrared spectrum image of chitosan, and Image 2 is the infrared spectrum image of the composite flocculant prepared in Example 1. Compared with the infrared image of chitosan, the infrared spectrum image of the composite flocculant prepared in Example 1 is 1380-1350cm -1 The characteristic peak at 1210-1190cm -1 There is an obvious characteristic peak of P=O at 1020-1000cm -1 There is an obvious characteristic peak of POC at 570-540cm -1 The characteristic peak of SS appeared, indicating that the composite flocculant prepared in Example 1 was successfully prepared.

[0060] Experimental Example 2

[0061] In this experimental example, the composite flocculant prepared in Example 1 was observed using a Zeiss-Supra 55 field emission scanning electron microscope to observe the morphology of the prepared particles. The dried microspheres were ground and applied to a sample stage, and then gold was sprayed. The microscopic morphology of the composite flocculant prepared in Example 1 is shown in FIG. Figure 2 As shown, chitosan has a rough surface, high surface area and loose pores, which is conducive to flocculation.

[0062] Experimental Example 3

[0063] In this experimental example, the composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to Zeta potential test, and a simulated water sample with ρ (kaolin) = 5 g / L was prepared. The composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 were made into an aqueous solution with a mass fraction of 0.5%, and the pH value of the simulated water sample was adjusted. 100 mL of the simulated water sample was placed in a four-way stirrer for measurement, and the parameters were set to stir at 120 rpm for 3 min, then stir at 50 rpm for 15 min, and finally settle for 30 min. After sedimentation, water samples were collected from the supernatant of the wastewater, and the potential changes of the supernatant after flocculation were analyzed by a Zeta potential analyzer (ZEN3690, Malvern Instruments Co., Ltd, UK).

[0064] Figure 3 The Zeta potential result diagram of the composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 at different pH values; as shown in the figure, under acidic conditions, due to the protonation reaction of the secondary amine group, the composite flocculant exhibits positive charge, and the Fe3O4 nanoparticles adsorb protons under acidic conditions, and their surfaces have positive charge. Due to the competitive adsorption of protons by the secondary amine group and the Fe3O4 nanoparticles, the protonation reaction rate of the secondary amine group is weakened, so that the potential of the composite flocculants prepared in the examples under acidic conditions is reduced. Under the same pH conditions, Comparative Example 1 does not contain phosphate groups, and the free hydrogen ions in the environment It can quickly undergo protonation reaction with secondary amine groups, thereby increasing the potential of the composite flocculant. Comparative Example 3 does not include Fe3O4 nanoparticles, which reduces the adsorption competition for protons and increases the potential of the composite flocculant. Under neutral conditions, the composite flocculant prepared in the embodiment has a negative potential, which can enhance the interaction with ions in the environment under neutral conditions. Under alkaline conditions, the phosphate group exhibits a strong negative potential. The SS bond contained in the cross-linking agent N,N'-bis(acryl)cystamine nitrogen is unstable under alkaline conditions. After the SS bond is broken, the negative charge of the flocculant can be increased. At the same time, the Fe3O4 nanoparticles have a strong negative potential for OH. -It has an adsorption effect, affects the negative charge of the phosphate group, weakens the electronegativity of the flocculant, and enables the flocculant to maintain a high stability within the range of pH changes.

[0065] Experimental Example 4

[0066] In this experimental example, the flocculation performance and regeneration performance of the composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 were tested. The composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 were made into aqueous solutions with a mass fraction of 1%, 100 mL of simulated water sample was placed in a four-way stirrer, and the composite flocculant was added to the simulated water sample at a dosage of 50 mg / L, the pH was adjusted to 8.0, the parameters were set to stir at 120 rpm for 3 min, then slowly stirred at 50 rpm for 15 min, and finally precipitated for 30 min. After precipitation, a water sample was collected from the supernatant of the wastewater, and its turbidity was measured. The precipitate was placed in a 1 mol / L hydrochloric acid solution for washing, the kaolin particles and the composite flocculant were separated, and after drying, the mass change rate of the composite flocculant was measured.

[0067] Figure 4 The flocculation performance and recycling performance of the composite flocculants prepared in Examples 1-3 and Comparative Examples 1-3 are shown in the figure. After being treated with the composite flocculants prepared in Examples 1-3, the turbidity of the simulated water samples was significantly reduced, and after recycling, the mass change rate was maintained at a high level. The flocculant prepared by the present invention has negative charge under neutral and alkaline conditions, and has high adsorption performance for clay particles and heavy metal ions with positive charges on its surface. In addition, under alkaline conditions, the rupture of disulfide bonds can increase the active sites on the surface of the composite flocculant. During the acid washing process, the disulfide bonds are repaired, which can improve the structural stability of the composite flocculant and improve its recycling performance.

[0068] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0069] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A composite flocculant for treating surface water, characterized in that: The raw materials for preparing the composite flocculant include the following components in parts by weight: 10-15 parts of Fe3O4 / chitosan, 30-40 parts of phosphorylated acrylate compound, 4-5 parts of N,N'-bis(acryloyl)cystamine, and 1-2 parts of initiator; The synthetic raw materials of the phosphating acrylate compound include the following components in parts by weight: 4-5 parts of 2-aminoethyl methacrylate hydrochloride, 10-12 parts of dimethyl phosphite, and 1-2 parts of formaldehyde; The preparation method of the phosphated acrylate compound specifically comprises the following steps: placing 2-aminoethyl methacrylate hydrochloride in a 95 vol% ethanol solution, stirring at a speed of 150 rpm until completely dissolved, adding dimethyl phosphite and mixing evenly, raising the temperature to 60-70°C, adding formaldehyde solution, mixing evenly, adding sodium p-toluenesulfonate, maintaining the reaction temperature at 70-80°C, and performing reflux reaction for 4-6 hours. After the reaction is completed, the reaction system is cooled to room temperature, distilled under reduced pressure, washed with anhydrous ethanol and deionized water, and freeze-dried to obtain the phosphated acrylate compound.

2. A composite flocculant for treating surface water according to claim 1, characterized in that: The initiator includes at least one of potassium persulfate and sodium persulfate.

3. A composite flocculant for treating surface water according to claim 1, characterized in that: The mass concentration of the 2-aminoethyl methacrylate hydrochloride in the ethanol solution is 10-15 g / L.

4. A composite flocculant for treating surface water according to claim 1, characterized in that: The added mass of the sodium p-toluenesulfonate is 10%-12% of the mass of 2-aminoethyl methacrylate hydrochloride.

5. The composite flocculant for treating surface water according to claim 1, characterized in that: The mass fraction of formaldehyde in the formaldehyde solution is 37%.

6. A method for preparing a composite flocculant for treating surface water according to any one of claims 1 to 5, characterized in that: The specific steps include: S1. Dissolve chitosan in acetic acid solution, add ferric chloride and ferrous chloride, stir and react until the reaction system turns brown, add 2 mol / L NaOH solution and 0.2 mol / L sodium citrate solution, mix well, age for 8-12 hours, and wash with deionized water until neutral to obtain Fe3O4 / chitosan; S2. The Fe3O4 / chitosan prepared in step S1 is placed in a 75 vol% ethanol solution, acetic acid is added, and after being fully mixed, nitrogen is introduced into the reaction system, an initiator is added, stirring is continued to make the reaction system uniform, phosphorylated acrylate compound and N,N'-bis(acryloyl)cystamine are added, the reaction temperature is increased to 50-60°C, and after reacting for 3-4 hours, the reaction system is cooled to room temperature, anhydrous ethanol is added for treatment, and the mixture is centrifuged at 4500-6000 rpm for 3-5 minutes, the supernatant is discarded, and the lower layer of the reaction product is washed with anhydrous ethanol, and dried to obtain a composite flocculant.

7. The method for preparing a composite flocculant for treating surface water according to claim 6, characterized in that: In step S1, the mass ratio of chitosan to ferric chloride is 1:1.5-1.8; the mass ratio of ferric chloride to ferrous chloride is 1:1.5-2.

8. The method for preparing a composite flocculant for treating surface water according to claim 7, characterized in that: In step S1, the volume ratio between the NaOH solution and the acetic acid solution is 1:2.5-3; the volume ratio between the sodium citrate solution and the acetic acid solution is 1:2-2.

3.

9. The method for preparing a composite flocculant for treating surface water according to claim 8, characterized in that: In step S2, the mass concentration of the Fe3O4 / chitosan in the ethanol solution is 10-20 g / L.

10. The method for preparing a composite flocculant for treating surface water according to claim 9, characterized in that: In step S2, the added volume of acetic acid is 1%-2% of the volume of the ethanol solution.

Citation Information

Patent Citations

  • Water-soluble phosphorylated chitosan and preparation method thereof

    CN113667038A

  • Chitosan-based flocculant for purifying water

    WO2023222175A1